Diagnostic Value of Sural Nerve Biopsy: Retrospective Analysis of Clinical Cases From 1981 to 2017 - Prada, Valeria; Massucco, Sara; Venturi, Consuelo; Geroldi, Alessandro; Bellone, Emilia; Mandich, Paola; Minuto, Michele; Varaldo, Emanuela; Mancardi, Giovanni; Grandis, Marina; Schenone, Angelo (Frontiers in Neurology, 2019)
Nerve biopsy represents the conclusive step in the diagnostic work-up of peripheral neuropathies, and its diagnostic yield is still debated. The aim of this study is to consider the impact of nerve biopsy on reaching a useful diagnosis in different peripheral neuropathies and its changing over time. We retrospectively analyzed 1,179 sural nerve biopsies performed in the period 1981–2017 at Neurological Clinic of Policlinico San Martino (Genoa). We relied on medical records and collected both clinical and pathological data in a database. Biopsy provided univocal diagnoses in 53% of cases (with an increase over time), multiple diagnostic options in 14%, while diagnosis was undetermined in 33% (undetermined reports decreased during the years). In 57% of patients, the pre-biopsy suspicion was confirmed, while in 43% sural biopsy modified the clinical diagnosis. The highest yield was in axonal neuropathies (29% undetermined reports vs. 40% in demyelinating and 48% in mixed neuropathies). In 68% of patients with vasculitic neuropathy, this etiology was already suspected, whereas in 32% nerve biopsy modified the clinical diagnosis. During the years, the number of annually performed biopsies decreased significantly (p = 0.007), with an increase in the mean age of patients (p < 0.0001). The percentage of hereditary neuropathies had a significant decrease (p = 0.016), while the rate of vasculitic and chronic inflammatory neuropathies increased (p < 0.0001). This is the largest Italian study addressing the yield of sural nerve biopsy. During the years, we observed a progressive refinement of the indication of this procedure, which confirms its utility for interstitial neuropathies, particularly if non-systemic vasculitic neuropathy is suspected.